Strategi Pemasaran Batu Bata di Kelurahan Sidomuly - Hanuarsyah, Dwi; Susena , Karona Cahya (Jurnal Kewirausahaan dan Bisnis, 2024)
making bricks is a small business engaged in the building materials industry. The challenge that must be faced is how to increase product sales and introduce Batu Bata to the community. Therefore, a community service program with the title "Marketing Strategy of "Batu Bata" in Sidomulyo Village, Bengkulu City" was conducted to assist business managers in designing marketing strategies that are in accordance with the characteristics of their business. This program aims to increase product sales and introduce bricks to the community. The implementation of marketing strategies is carried out with several steps, such as creating a brand identity for the Batu Bata business, using social media as a means of promotion, and developing a distribution network. Brand identity is made to introduce Batu Bata more clearly and present among building raw materials, while the use of social media is done so that consumers easily recognize and remember the good use of sturdier bricks. Distribution network development is carried out to expand market share and expand product reach to consumers. From the evaluation results, the community service program with the title "Marketing Strategy for Bricks in Sidomulyo Village, Bengkulu City" succeeded in having a positive impact on the continuity of the MSME business. The implementation of the right marketing strategy has succeeded in increasing the number of product sales and increasing awareness of Batu Bata in the community. In addition, this program also helps MSMEs to expand distribution networks and optimize the use of social media as a means of promotion. Thus, the implementation of effective marketing strategies can be a solution for MSMEs in facing increasingly competitive market competition.